Development of Character Assessment Instruments for Elementary School Students in Sikka Regency in Mathematics Subjects Materials for Flat Shapes Based on Android Applications - Emerentiana, Paula; Lestari, Wahyu; Sugiyo Pranoto, Yuli Kurniawati (Universitas Negeri Semarang, 2022)
Development of Character Assessment Instruments for Elementary School Students in Sikka Regency in Mathematics Subjects Materials for Flat Shapes Based on Android Applications is a development research with the formulation of the problem, namely: The assessment model used by the teacher, Design of developing student character assessment instruments, Validity, Reliability and Practicality of student character assessment instruments on Android-based flat-building math subjects. The purpose of the study was to produce an instrument for assessing the character of elementary school students in Sikka Regency based on a valid, reliable, and practical android application. The research method uses research and development (R&D). The development using the Djemari Mardapi model was modified in three stages: the preliminary stage, the development stage, and the evaluation stage. The results of the study resulted in a teacher's guidebook and the application of student character assessment instruments in valid, reliable, and practical mathematics subjects, the instrument was validated by a validator to test the feasibility of the instrument, reliability was analyzed by intraclass correlation coefficients obtained by an average limited trial of 0.783. Large-scale trials average 0.868 and average measure 0.906. One-way ANOVA statistical test obtained a valid value of 0.85. Practicality test highest score 80 practical. In conclusion, the development research resulted in a teacher's guidebook and an application for character assessment for elementary school students in mathematics. Suggestions for teachers to use guidebooks and applications that have been downloaded via Smartphones in classroom learning when conducting learning evaluations.